Structural and functional maturation of cardiomyocytes derived from human pluripotent stem cells - Lundy, Scott D; Zhu, Wei-Zhong; Regnier, Michael; Laflamme, Michael A (Stem cells and development, 2013)
Despite preclinical studies demonstrating the functional benefit of transplanting human pluripotent stem cell-derived cardiomyocytes (PSC-CMs) into damaged myocardium, the ability of these immature cells to adopt a more adult-like cardiomyocyte (CM) phenotype remains uncertain. To address this issue, we tested the hypothesis that prolonged in vitro culture of human embryonic stem cell (hESC)- and human induced pluripotent stem cell (hiPSC)-derived CMs would result in the maturation of their structural and contractile properties to a more adult-like phenotype. Compared to their early-stage counterparts (PSC-CMs after 20-40 days of in vitro differentiation and culture), late-stage hESC-CMs and hiPSC-CMs (80-120 days) showed dramatic differences in morphology, including increased cell size and anisotropy, greater myofibril density and alignment, sarcomeres visible by bright-field microscopy, and a 10-fold increase in the fraction of multinucleated CMs. Ultrastructural analysis confirmed improvements in the myofibrillar density, alignment, and morphology. We measured the contractile performance of late-stage hESC-CMs and hiPSC-CMs and noted a doubling in shortening magnitude with slowed contraction kinetics compared to the early-stage cells. We then examined changes in the calcium-handling properties of these matured CMs and found an increase in calcium release and reuptake rates with no change in the maximum amplitude. Finally, we performed electrophysiological assessments in hESC-CMs and found that late-stage myocytes have hyperpolarized maximum diastolic potentials, increased action potential amplitudes, and faster upstroke velocities. To correlate these functional changes with gene expression, we performed qPCR and found a robust induction of the key cardiac structural markers, including β-myosin heavy chain and connexin-43, in late-stage hESC-CMs and hiPSC-CMs. These findings suggest that PSC-CMs are capable of slowly maturing to more closely resemble the phenotype of adult CMs and may eventually possess the potential to regenerate the lost myocardium with robust de novo force-producing tissue.